On some properties of Buhmann functions - Zastavnyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study functions introduced by Buhmann. The exact exponent of smoothness of these functions is obtained and the problem of positivity of their Hankel transforms is analyzed.